Nutrition information collection and management system using participatory approach for community health awareness - Tai, Loo Ping (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Nutrition intake is now gaining attention by public as more and more people are infected with incurable diseases nowadays. So, there are lots of people who search for nutrition information via many platform such as internet. But, most of the nutrition information available in internet may dubious because only webmaster validate those information. So, the proposed system, a nutrition information collection and management system which applied community-based participatory approach, enable people to search for nutrition information and at the same time they become validator of all of the nutrition information available in the system. With this system, the incorrect nutrition information will be minimized. People will be involve into the system by community-based participatory approach. I